Performance of a new fully automated transthoracic three‐dimensional echocardiographic software for quantification of left cardiac chamber size and function: Comparison with 3 Tesla cardiac magnetic resonance. Issue 9 (29th July 2019) - Levy, Franck; Iacuzio, Laura; Schouver, Elie D.; Essayagh, Benjamin; Civaia, Filippo; Dommerc, Carinne; Maréchaux, Sylvestre
Abstract: Purpose: To evaluate the accuracy and reproducibility of a new fully automated fast three‐dimensional (3D) transthoracic echocardiography (TTE) software for the simultaneous assessment of left atrial (LA) volumes and LA ejection fraction (EF), left ventricular (LV) volumes, LV mass, and LVEF, and to compare the results obtained with a cardiac magnetic resonance (CMR) reference. Methods: We included retrospectively 56 patients (46 men; mean age 63 ± 13 years) in sinus rhythm who had had comprehensive 3D TTE and CMR examinations within 24 hours. Results: Despite a slight underestimation of LV and LA volumes, LVEF and LAEF were similar using CMR or 3DTTE (58% ± 16% vs 58% ± 12%; P = .65 and 45% ± 14% vs 46% ± 15%; P = .38, respectively) in the total population. Despite significant correlation between TTE and CMR measurements ( r = 0.78; P < .001), 3D TTE underestimated LV mass (bias = −27 ± 35 g). Conclusion: 3D TTE using a new‐generation fully automated software is a fast and reproducible imaging modality for simultaneous extensive quantification of left heart chambers size and function in routine practice. Potential underestimation of LA volume and LV mass, and of LVEF in patients with LVEF <50%, should be taken into consideration.